Study of Reproductive Physiology of Male Fruit Bat Rousettus leschenaulti (Desmerest): A Conservation Effort of a Crucial Pollinator - Masram, Archana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Rousettus leschenaulti- a Indian fruit bat plays an important role in pollination due to its frugivorous habit. The conservation of this bat has a significant importance in the conservation and proliferation of flora of the geographical region. This study investigates the relationship between Luteinizing Hormone (LH) and Serum Testosterone levels in male fruit bats (Rousettus leschenaulti). It's important to understand this connection to grasp reproductive physiology in bats, which could also shed light on broader mammalian endocrinology. Analysis of blood samples from male bats was done using enzyme-linked immunosorbent assay (ELISA) to measure LH and testosterone levels. Our statistical analysis revealed a significant positive correlation between LH and testosterone levels (r = 0.95, p < 0.05), suggesting that LH plays a vital role in regulating testosterone production in this species. This finding adds to our understanding of reproductive hormone dynamics in bats and highlights potential similarities with other mammals.